Enpp2 Expression by Dendritic Cells Is a Key Regulator in Migration - Jun-Ho Lee (MDPI AG, 2021)
Enpp2 is an enzyme that catalyzes the conversion of lysophosphatidylcholine (LPC) to lysophosphatidic acid (LPA), which exhibits a wide variety of biological functions. Here, we examined the biological effects of Enpp2 on dendritic cells (DCs), which are specialized antigen-presenting cells (APCs) characterized by their ability to migrate into secondary lymphoid organs and activate naïve T-cells. DCs were generated from bone marrow progenitors obtained from C57BL/6 mice. Enpp2 levels in DCs were regulated using small interfering (si)RNA or recombinant Enpp2. Expression of Enpp2 in LPS-stimulated mature (m)DCs was high, however, knocking down Enpp2 inhibited mDC function. In addition, the migratory capacity of mDCs increased after treatment with rmEnpp2; this phenomenon was mediated via the RhoA-mediated signaling pathway. Enpp2-treated mDCs showed a markedly increased capacity to migrate to lymph nodes in vivo. These findings strongly suggest that Enpp2 is necessary for mDC migration capacity, thereby increasing our understanding of DC biology. We postulate that regulating Enpp2 improves DC migration to lymph nodes, thus improving the effectiveness of cancer vaccines based on DC.